AFLPmatrix_orginal_Betula_pub_alle_332_155 - Eidesen, Pernille Bronken; Alsos, Inger Greve; Brochmann, Christian (Dryad Digital Repository, 2015)
Binary AFLP matrix with 155 markers, 332 individuals of mainly Betula pubescens, but also including reference species and hybrids generated by 3 primer combinations